Solomon Islands : Request for an Extension of the Arrangement Under the Extended Credit Facility; Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Solomon Islands' Request for an Extension of the Arrangement Under the Extended Credit Facility (ECF). All end-December 2014 performance criteria (PCs), indicative targets (ITs) for March 2015, and end-June 2015 PCs have been met by a considerable margin, with the exception of the ITs on government-funded recurrent spending on health and education, which have been consistently missed since 2014 albeit by a small margin. September 2015 available data indicate that ITs on international reserves, net domestic assets at the Central Bank, and net credit to the government have been comfortably met. The authorities remain committed to macroeconomic stability and completion of the reviews.